The impact of paintings hung on lecture room walls on the speech intelligibility and perception of background noise. Issue 4 (July 2016) - Čudina, Mirko; Prezelj, Jurij; Pušlar-Čudina, Milena
The most important parameter for rooms designed for speech (classroom or lecture room) is speech intelligibility. Speech intelligibility depends on the reverberation time, speech-to-noise ratio and geometry of the room, among others. At the Faculty of Mechanical Engineering, University of Ljubljana, the reverberation times in lecture rooms observed exceed the optimal value from 0.31 to 0.87 s and in some of them, speech intelligibility is below the threshold of good or even satisfactory. For reducing reverberation time and improving speech intelligibility, an alternative method was proposed, by hanging art paintings on the room walls. Experiments have shown that by doing so, reverberation time can be reduced by increasing the absorption coefficient by more than 30% in the most audible part of the frequency spectra (between 500 and 1500 Hz). The absorption coefficient can be increased by using different dimensions of paintings, different air spaces behind the canvas, by appropriate thickness of the paint layers and by adding absorption material behind the canvas. Subjective tests have also shown that paintings with proper colour combinations (pastel colours with prevailing green, blue and grey colours) are appropriate for soothing the undesirable effect of background sound (noise) by changing perception in the brain.